(18)F-Fluorodeoxyglucose Positron Emission Tomography-Computed Tomography Imaging of Inferior Vena Cava Tumor Thrombus Extending into the Right Atrium in a Patient with Cholangiocarcinoma Treated with (90)Y-Microspheres - Filippi, Luca (Indian J Nucl Med, 2018)
We present a case of a 42-year-old male patient affected by unresectable, chemorefractory cholangiocarcinoma, with prior placement of biliary stent. Because of the absence of extrahepatic metastases, he was submitted to liver-direct therapy with (90)Y-microspheres. (18)F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT) performed before the procedure showed intense tracer uptake in the hepatic lesion and along the biliary stent. The patient underwent radioembolization with (90)Y-resin spheres (1.1 GBq). (18)F-FDG PET-CT, acquired 6 weeks after the procedure, showed no response of the hepatic lesion and the appearance of an area of markedly increased uptake extending through the inferior vena cava into the right atrium, confirmed as extensive tumor thrombus at the enhanced multislice CT subsequently performed. (18)F-FDG PET-CT proved to be a useful imaging tool not only for the evaluation of metabolic response but also for the early detection of extrahepatic progression after 90Y-radioembolization.